Risks in export deliveries of SMEs - V. V. Balakirev; E. Yu. Kamchatova (Путеводитель предпринимателя)
The article is devoted to the analysis of the main risks associated with export deliveries by small and medium–sized industrial enterprises. Of all the many risks that arise in foreign trade deliveries of SMEs, the author identifies two large groups: a priori risks, which are a theoretical plan for working out certain commercial issues of the company’s entry into the foreign market, and a posteriori risks, which become known to the business entity only after entering a foreign market, organizing a specific supply chain, conducting an advertising campaign, etc. The described risk groups — apriori, aposteriori, most specific level — the level of commercial risks of an enterprise engaged in foreign trade deliveries.